LANGUAGE AND COMMUNICATION TEACHING AT BUSINESS SCHOOL: NEW PERSPECTIVES - MAMATALIEVA XULKAROY MURODJONOVNA (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper represents the redesigned language and communication program for bachelor students. The research of the high school stakeholders’ needs specified the skills that help to formulate new skills agenda. The analysis predetermines the modification of the language and communication program. The paper provides an opportunity to advance the understanding of perspectives in language and communication program development